1993
DOI: 10.1002/nur.4770160305
|View full text |Cite
|
Sign up to set email alerts
|

Themes of loss and dying in caring for a family member with AIDS

Abstract: The study purpose was to provide an in-depth description of experiences associated with loss and dying among AIDS family caregivers. Grounded theory provided the methodological framework for data collection and analysis. In-depth interviews were conducted with 53 family caregivers of persons with AIDS and included individuals from family of origin and family of choice. Living with loss and dying was identified as a major substantive category and was further explicated in two subcategories: facing loss and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Anticipating the loss of the spouse was the most painful aspect of loss for these women as has been found in other research (Ross & Graydon 1997, Bergs 2002. Similar to the findings in this study, Brown and Powell-Cope (1993) identified anger as a feature of loss in caregivers of persons with AIDS, with anger 'often related to untimely death and/or to the PWA's (person with AIDS) responsibility for contracting AIDS ' (p. 184). This illustrates the similarity in stigmatising effects of AIDS and COPD, as these two diseases are usually attributed to lifestyle choices.…”
Section: Discussionsupporting
confidence: 88%
“…Anticipating the loss of the spouse was the most painful aspect of loss for these women as has been found in other research (Ross & Graydon 1997, Bergs 2002. Similar to the findings in this study, Brown and Powell-Cope (1993) identified anger as a feature of loss in caregivers of persons with AIDS, with anger 'often related to untimely death and/or to the PWA's (person with AIDS) responsibility for contracting AIDS ' (p. 184). This illustrates the similarity in stigmatising effects of AIDS and COPD, as these two diseases are usually attributed to lifestyle choices.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, Parkes and Weiss (1983) reported that anticipatory grief can increase involvement in relationships by drawing people together. This notion was supported by Brown and Powell-Cope's (1993) report that open discussion of death can be quite fulfilling, sometimes resulting in increased cohesion among family members.…”
Section: Disclosurementioning
confidence: 81%
“…Given that the death of one's chdd is presumed to lead to the most acute type of stress (Sanders, 1979), the anguish resulting &om providing care to a loved one who is HIV positive would be particularly intense when the loved one is the mother's child (O'Donnell & Bernier, 1990). Those who care for others with AIDS are vulnerable and should benefit fiom support and or counseling (Brown & Powell-Cope, 1993). Unfortunately, it is quite likely that most women who are HIV positive and caring for another 111 person do not have the emotional or financial resources to obtain either support or counseling.…”
Section: Mother's Other Caregiving Burdensmentioning
confidence: 99%
“…Also, issues related to HIV/AIDS death as a form of relief were critical in shaping existential perceptions of women in this study. The emotional toll on family members of PLWHA is enormous as they observe the pain and suffering endured by the PLWHA before they ultimately succumb to death from AIDS (Brown & Powell-Cope, 1993). Family members' belief that death is a form of relief invariably becomes their unique response to the eventual loss of family from HIV.…”
Section: Discussionmentioning
confidence: 99%